The Role of Imaging Modalities in Determining Surgical Management of Breast Cancer: A Literature Review - Raihan Aulia Arbani; Dwi Pratiwi; Adhelia Purnamawati Harifuddin; Hasliyawati Hasan; Ana Meliyana M (Newinera Publisher, 2026)
Breast cancer is one of the most common malignancies among women and remains a major cause of morbidity and mortality worldwide. Because breast cancer may develop without obvious symptoms in its early stages, accurate imaging assessment is essential to support early detection, disease staging, and appropriate treatment planning. Imaging modalities such as mammography, ultrasonography, magnetic resonance imaging (MRI), dynamic contrast-enhanced MRI (DCE-MRI), and artificial intelligence-based imaging technologies play an important role in evaluating tumor size, lesion characteristics, disease extent, multifocality, and treatment response. This study aimed to examine the role of imaging modalities in determining surgical management for breast cancer. This study employed a narrative literature review with PRISMA-guided article selection. Literature was collected through searches in PubMed, Google Scholar, Garuda, and other relevant scientific databases using selected keywords, including breast cancer, imaging modalities, mammography, ultrasonography, magnetic resonance imaging, MRI, DCE-MRI, surgical management, and surgical planning. Based on the screening process, 11 articles consisting of 4 national and 7 international journals were included in the review. The findings indicate that mammography is important for early detection, ultrasonography supports lesion characterization and clinical decision-making, while MRI and DCE-MRI provide more detailed information regarding tumor extent, local staging, multifocal lesions, and response to neoadjuvant therapy. Artificial intelligence-based imaging also shows potential in improving diagnostic accuracy and supporting individualized surgical planning. Therefore, imaging modalities are not only diagnostic tools but also strategic components in determining the type and extent of surgical treatment in breast cancer patients.